2021
DOI: 10.1038/s41467-021-22521-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of eviction moratoria on the transmission of SARS-CoV-2

Abstract: Massive unemployment during the COVID-19 pandemic could result in an eviction crisis in US cities. Here we model the effect of evictions on SARS-CoV-2 epidemics, simulating viral transmission within and among households in a theoretical metropolitan area. We recreate a range of urban epidemic trajectories and project the course of the epidemic under two counterfactual scenarios, one in which a strict moratorium on evictions is in place and enforced, and another in which evictions are allowed to resume at basel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 63 publications
1
40
0
1
Order By: Relevance
“…
The coronavirus (COVID-19) pandemic precipitated an economic crisis in the United States that, as a function of the sectors most severely affected, has had a disproportionate impact on renter households (Airgood-Obrycki and Hermann 2021; Kneebone and Murray 2020). As concern grew that job losses might put a growing number of families at risk for eviction, and recognizing that a spike in evictions would likely exacerbate the spread of COVID-19 (Benfer et al 2021;Leifheit et al 2020;Nande et al 2021), policy makers at the federal, state, and local levels initiated an unprecedented array of interventions intended to support residential stability, including temporary eviction moratoria. These policies varied considerably in terms of what protections were afforded, to whom, and for what duration ), but at least initially, they shared a common goal: to prevent housing instability during the public health emergency.This article offers a snapshot of eviction filing patterns in 2020 and a first description of the efficacy of these interventions.
…”
mentioning
confidence: 99%
“…
The coronavirus (COVID-19) pandemic precipitated an economic crisis in the United States that, as a function of the sectors most severely affected, has had a disproportionate impact on renter households (Airgood-Obrycki and Hermann 2021; Kneebone and Murray 2020). As concern grew that job losses might put a growing number of families at risk for eviction, and recognizing that a spike in evictions would likely exacerbate the spread of COVID-19 (Benfer et al 2021;Leifheit et al 2020;Nande et al 2021), policy makers at the federal, state, and local levels initiated an unprecedented array of interventions intended to support residential stability, including temporary eviction moratoria. These policies varied considerably in terms of what protections were afforded, to whom, and for what duration ), but at least initially, they shared a common goal: to prevent housing instability during the public health emergency.This article offers a snapshot of eviction filing patterns in 2020 and a first description of the efficacy of these interventions.
…”
mentioning
confidence: 99%
“…The result of the sensitivity analysis showing no association of expiring eviction moratoria on the hazard of individuals in this data set changing zip codes is consistent with previous findings in the literature, ie, an individual's hazard of COVID-19 diagnosis was not just affected by personal experiences with eviction but also by spillovers from the transmission process created by evictions within a community. 5 While previous ecological evidence…”
Section: Discussionmentioning
confidence: 99%
“…The result of the sensitivity analysis showing no association of expiring eviction moratoria on the hazard of individuals in this data set changing zip codes is consistent with previous findings in the literature, ie, an individual’s hazard of COVID-19 diagnosis was not just affected by personal experiences with eviction but also by spillovers from the transmission process created by evictions within a community. 5 While previous ecological evidence showed that area-level COVID-19 incidence increases after eviction moratoria are lifted, 4 these county-level analyses have not been able to answer the question of who, specifically, is put at risk by allowing evictions to occur during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as various eviction moratoriums throughout the US have lapsed during the pandemic, eviction filings have exceeded historical averages (Hepburn et al, 2021). Emerging evidence suggests that COVID-19 eviction moratoriums have helped to mitigate the spread of the virus and prevent housing displacement, though much of this evidence is preliminary and more work in this area is needed (Benfer et al, 2020;Jowers et al, 2021;Leifheit et al, 2020;Nande et al, 2021).…”
Section: Introductionmentioning
confidence: 99%